PELAKSANAAN MODEL TARL DALAM PEMBELAJARAN TEMATIK KELAS IV MADRASAH IBTIDAIYAH SAMBINAE KOTA BIMA - Iis puspitasari; Agussalam; Fuaddudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Teaching at the Right Level (TARL) model in thematic learning for fourth grade students at Madrasah Ibtidaiyah Sambinae, Bima City. The main problem studied is how the implementation of the TARL model in thematic learning at Madrasah Ibtidaiyah Sambinae, Bima City and what are the supporting and inhibiting factors for thematic learning at MI Sambi Nae, Bima City. The research method used is a qualitative approach with data collection techniques through interviews, observation of learning activities, and documentation. Data were analyzed using descriptive analysis techniques. The TARL model is an approach that places students in learning groups based on their level of mastery of the material, not based on age or class. This study aims to determine how the TARL model is applied by teachers in the learning process, as well as its impact on student involvement and understanding. The results of this study conclude that the application of the TARL model helps teachers in adjusting learning strategies to students' actual abilities. Students are more actively involved in the learning process and show an increase in understanding the material.